Proces vsebinske analize pri katalogizaciji knjižničnega gradiva - Kos, Jelka (Knjižnica, 2011)
Purpose: The study tried to answer how catalogers determine the subject of a document. The aim of the research is to understand: (1) which parts of document are most important in the subject analysis process, (2) which approaches in the subject determination are involved, (3) which features of document are most significant, (4) which stages and cognitive processes are present, and, (5) if and how the subject analysis process of catalogers at Slovenian academic libraries differ from conceptions described in textbooks and ISO 5963 standard. Methodology/approach: Ten catalogers from nine Slovenian academic libraries were included qulitative research. Observation, think-aloud procedures, diaries and follow up discussions (non-structured interviews) were used for collecting data. Results: Regarding the parts of the document the participants mostly look at title, table of contents, introduction/preface and checking the entire document. The document-oriented approach to subject determination was predominant. There were four stages in the process noted: the data input, data processing, text reduction and finishing the subject determination process. Based on the results two general models of the subject analysis process were constructed. Research limitation: The small and convenient sample limits the generalization of findings. Originality/practical implications: It is a rare empirical study with qualitative approach in researching the subject analysis in Slovenia.
Keywords: vsebinska analiza; vsebinska obdelava; katalogizacija; visokošolske knjižnice; kvalitativno raziskovanje; raziskave; Slovenia; Slovenija